STATUS OF SUSTAINABILITY OF ORGANIC RICE COMMODITIES AS RURAL ECONOMIC POTENTIAL IN BONDOWOSO REGENCY - Diartho, Herman Cahyo (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2024)
The complexity of organic farming system problems starts from the increasingly scarce availability of land resources, farmers' business capital which is still very limited and marketing access and the organic rice market chain, population growth continues to increase every year and the low quality of community resources, and knowledge in the application of technology and quality standardization will impact on the sustainability of organic rice commodities. The aim of this research is to analyze the sustainability status of organic rice commodities in terms of ecological, economic and social dimensions. The analytical method used in this research is Rapfish which is modified into RAP-Organic rice using the Multidimensional scaling method. The results of research on the multi-dimensional sustainability status of organic rice commodities including ecological, economic, social and infrastructure & technology dimensions show that organic rice commodities have a fairly sustainable index value with an index value of 73.58, meaning that with this index value all dimensions include: ecological dimension, economic, social and infrastructure & technology influence the sustainability status of organic rice commodities. The implication of the analysis results is that the Regional Government needs to increase attention to organic rice farmer groups regarding the importance of organic rice businesses by making special policies for the development of organic rice businesses to continue to increase the sustainability of organic rice commodities.